Scale : seven proven principles to grow your business and get your life back - Hoffman, Jeff; Finkel, David (New York : Portfolio Hardcover, 2014)
"Business owners want growth, but they fear that growth will take over their lives. The surprising truth is that the only way to truly scale your company is to reduce its reliance on you. This means that, done right, you get growth without sacrificing your life. Jeff Hoffman and David Finkel offer a concrete road map to rapidly grow your existing business while also gaining more freedom. You'll learn the three core elements to create a stable base from which to scale (systems, team, and internal controls), how to pick the best strategy to get smart growth, and how to remove the predictable obstacles to scaling pillar by pillar inside your business. Plus you'll also get practical, proven advice on how to execute in the face of conflicting demands and multiple responsibilities. By breaking down the path to scaling into seven principles, any business owner can increase profits and their own freedom"--
Includes index.
Keywords: Small business -- Growth; Corporations -- Growth; Strategic planning; Business planning; Entrepreneurship; BUSINESS & ECONOMICS / Small Business; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Management